2003
DOI: 10.1177/0891243203253962
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Menopause, and Culture

Abstract: Past research finds that after menopause some women experience negative changes such as vaginal dryness, decreased libido, and decreased orgasm quality; very little research inquires about positive changes. In contrast, this study shifts the research focus from whether women experience menopausal changes to how women view any changes in sex life. Based on 30 in-depth interviews with heterosexual and lesbian women, the author finds that most women emphasize cultural and social issues, such as relationship statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(13 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Equally, the high representation of women partners in this factor supports previous research which reported that a significant proportion of women partners of men with prostate cancer did not encourage help-seeking for a sexual problem, with many women resigned to, or accepting of, sexual changes [60]. Sex which is less focused on penetration, and more focused on other forms of intimacy, has also been reported to be preferred by many midlife and older women [66-68], with hugging, kissing, touching [69], as well as relationship closeness [70], being included in definitions of sex. Cancer may serve to legitimate such women resisting the coital imperative, and exploring non-coital, non-genital intimacy.…”
Section: Discussionsupporting
confidence: 67%
“…Equally, the high representation of women partners in this factor supports previous research which reported that a significant proportion of women partners of men with prostate cancer did not encourage help-seeking for a sexual problem, with many women resigned to, or accepting of, sexual changes [60]. Sex which is less focused on penetration, and more focused on other forms of intimacy, has also been reported to be preferred by many midlife and older women [66-68], with hugging, kissing, touching [69], as well as relationship closeness [70], being included in definitions of sex. Cancer may serve to legitimate such women resisting the coital imperative, and exploring non-coital, non-genital intimacy.…”
Section: Discussionsupporting
confidence: 67%
“…We were told by nearly all the women over 50 that they were now too old for a new relationship. Reduced sexual desire at menopause is well-documented (Sarrel 1990;Winterich 2003;Wood, Mansfield, and Koch 2007). For Uganda, Wolff, Blanc and Gage (2000, 315), catalogue some 'culturally mandated periods' during which women may refuse sex including menstruation, pregnancy, breast-feeding and also, significantly for older women, after menopause.…”
Section: Those Without Partnersmentioning
confidence: 97%
“…As Winterich (2003) infers, however, very little research explores the positive sexual changes during the climacteric period.…”
Section: Our Aim In Conducting This Study Is To Describe the Represenmentioning
confidence: 99%